The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1999
DOI: 10.1093/genetics/152.4.1679
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Quantitative Trait Loci for Backfat Thickness and Intramuscular Fat Content in Pigs (Sus scrofa)

Abstract: In an experimental cross between Meishan and Dutch Large White and Landrace lines, 619 F2 animals and their parents were typed for molecular markers covering the entire porcine genome. Associations were studied between these markers and two fatness traits: intramuscular fat content and backfat thickness. Association analyses were performed using interval mapping by regression under two genetic models: (1) an outbred line-cross model where the founder lines were assumed to be fixed for different QTL alleles; an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
12
1
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 267 publications
(21 citation statements)
references
References 30 publications
(6 reference statements)
7
12
1
1
Order By: Relevance
“…Breeding objectives for different breeds may have changed the allelic distribution of the H-FABP RFLPs. Previously, Janss et al (1997), De Koning et al (1999) andBo Zuo et al (2003) found some evidence suggestive of QTL and a major gene affecting IMF content. Findings from this study with Laiwu Black and four western breeds support the association of H-FABP genetic variation with intramuscular fat content (Gerbens et al, 1999).…”
Section: Discussionmentioning
confidence: 97%
“…Breeding objectives for different breeds may have changed the allelic distribution of the H-FABP RFLPs. Previously, Janss et al (1997), De Koning et al (1999) andBo Zuo et al (2003) found some evidence suggestive of QTL and a major gene affecting IMF content. Findings from this study with Laiwu Black and four western breeds support the association of H-FABP genetic variation with intramuscular fat content (Gerbens et al, 1999).…”
Section: Discussionmentioning
confidence: 97%
“…Sur le chromosome 2, le locus de teneur en muscle est localisĂ© dans la rĂ©gion du gĂšne IGF-2, pour laquelle des effets similaires ont Ă©tĂ© mis en Ă©vidence dans des croisements Large White x PiĂ©train (Nezer et al 1999) et Large White x sanglier (Jeon et al 1999). Des QTL pour les caractĂšres de croissance et l'Ă©paisseur de lard dorsal ont Ă©tĂ© mis en Ă©vidence ou suggĂ©rĂ©s dans la mĂȘme rĂ©gion du chromosome 4 par Andersson et al (1994) De mĂȘme, Wang et al (1998), Rohrer et Keele (1998aet 1998b et de Koning et al (1999) rapportent l'existence d'un QTL d'Ă©paisseur de lard dorsal dans la mĂȘme rĂ©gion du chromosome 7 que la prĂ©sente Ă©tude. Enfin, un QTL de composition corporelle est Ă©galement dĂ©tectĂ© sur le chromosome X par Rohrer et Keele (1998aet 1998b.…”
Section: / Analyses Statistiquesunclassified
“…Following this, QTL for growth and fat deposition traits (Paszek et al, 1999;Rohrer, 2000;Wada et al, 2000;Bidanel et al, 2001;Malek et al, 2001a), for carcass traits (Andersson-Eklund et al, 1998;Rohrer et al, 1998b), and for meat quality (De Koning et al, 1999Malek et al, 2001b) have been reported. QTL affecting reproduction traits in swine have been reported by Rathje et al (1997) and Wilkie et al (1999).…”
Section: Introductionmentioning
confidence: 96%